Soccer world - Rothman, Scott (Candlewick Press, 2026)
"Twins Pete and Zoe live and breathe soccer. Pete is an all-star goalie, covering angles, batting away balls, and diving for saves on his way to a shutout. Zoe is the team's best striker, dekeing defenders, crushing corner kicks, and nutmegging the other goalie for a hat trick. But no matter how good they are at what they do, they're always arguing about whose job is more important on the field. Until one day, when a magical rolling ball whisks them off to a fantastical place called Soccer World, where everyone plays the game all day and all night. It's amazing! But can Pete and Zoe find a way to appreciate each other's talents and work together in order to win the championship?" --